Analysis of fracture phenomena in concrete structures by means of cohesive modeling techniques - De Maio, Umberto; Critelli, Salvatore; Greco, Fabrizio; Nevone Blasi, Paolo (Università della Calabria, 2021)
Still today, the fracture phenomenon in cementitious materi-als is a research topic widely investigated by numerous research-ers in materials and structural engineering, since it involves many theoretical and practical aspects concerning both strength and durability properties of common concrete structures. In-deed, cracking is one of the main causes of the severe deteriora-tion of concrete structures, usually leading to an unacceptable re-duction of their serviceability time. The fracture processes, in-cluding onset, propagation, and coalescence of multiple cracks, arise in the structural members because of the low tensile strength of concrete, which is ultimately related to the existence of voids or undetected defects in the material microstructure.Such cracking processes significantly affect the global mechani-cal behavior of the concrete structures and may facilitate the in-gress of corrosive media; therefore, in the scientific community there is a strong interest in reducing cracks width to a minimum or in preventing cracking altogether. In the technical literature, several simplified numerical models, based on either linear-elas-tic or elastic-plastic fracture mechanics, are proposed to predict the fracture mechanisms during any stage of the lifetime of con-crete structures. However, the application of these models is somehow limited, due to their incapacity to capture the complex inelastic mechanical behavior of reinforced concrete members, involving multiple concrete cracking and steel yielding and their mutual interaction under the combined action of axial and bend-ing loadings. This thesis aims to develop a sophisticated numerical frac-ture model to predict the cracking processes in quasi-brittle ma-terials like concrete, and the main failure mechanisms of the re-inforced concrete structures in a comprehensive manner. The proposed methodology relies on a diffuse interface model (DIM), based on an inter-element cohesive fracture approach, where co-hesive elements are inserted along all the internal mesh bounda-ries to simulate multiple cracks initiation, propagation and coa-lescence in concrete. Such a model, is used in combination with an embedded truss model (ETM) for steel reinforcing bars in the failure analysis of reinforced concrete structures. In particular, truss elements equipped with an elastoplastic constitutive be-havior are suitably connected to the concrete mesh via a bond-slip interface, in order to capture the interaction with the sur-rounding concrete layers as well as with the neighboring propa-gating cracks. The proposed fracture model takes advantage of a novel mi-cromechanics-based calibration technique, developed and pro-posed in this thesis, to control and/or reduce the well-known mesh dependency issues of the diffuse cohesive approach, re-lated to the artificial compliance in the elastic regime. In this way, the initial stiffness parameters of the cohesive element employed in the diffuse interface model are suitably calibrated by means of a rigorous micromechanical approach, based on the concept of representative volume element. In particular, by performing sev-eral micromechanical analyses two charts have been constructed which provide the dimensionless normal and tangential stiffness parameters as functions of both the Poisson’s ratio of the bulk and the admitted reduction in the overall Young’s modulus after the insertion of the cohesive interfaces. The proposed fracture model has been firstly validated by performing numerical analysis in plain concrete elements, and secondly, employed to analyze the failure mechanisms in exter-nally strengthened reinforced concrete beams. In particular, several numerical simulations, involving pre-notched concrete beams subjected to mode-I loading conditions, have been performed to investigate the capability of the diffuse interface model to predict self-similar crack propagation and to assess the mesh-induced artificial toughening effects, also intro-ducing two new fracture models for comparison purpose. More-over, sensitivity analyses with respect to the mesh size and the mesh orientation have been performed to investigate the mesh dependency properties of the proposed fracture model. Further validation of the proposed diffuse interface model has been pro-vided for plain concrete structures subjected to general mixed-mode loading conditions. The role of the mode-II inelastic parameters (i.e. critical tangential stress and mode-II fracture en-ergy) on the nonlinear behavior of the embedded cohesive inter-faces is investigated in a deeper manner. In particular, two sen-sitivity analyses have been performed by independently varying the mode-II inelastic parameters required by the traction-separa-tion law adopted in the proposed concrete fracture model, in or-der to quantify the above-mentioned artificial toughening effects associated with mode-II crack propagation. Moreover, compari-sons with numerical and experimental results, with reference to mode-I and mixed-mode fracture tests, have been reported, highlighting the effectiveness of the adopted diffuse interface model (DIM) in predicting the failure response in a reliable man-ner. Subsequently, the integrated fracture approach is success-fully employed to predict the nonlinear response of (eventually strengthened) reinforced concrete beams subjected to general loading conditions. Firstly, the failure analysis of reinforced con-crete (RC) beams has been performed to assess the capability of the integrated fracture model to capture multiple crack initiation and propagation. Detailed stress analysis of the tensile reinforce-ment bars has been also reported to verify the capability of the embedded truss model (ETM) of capturing the tension stiffening effect. Secondly, the well-known concrete cover separation phe-nomenon has been predicted by performing complete failure simulations of FRP-strengthened RC elements. To this end, a sin-gle interface model (SIM) has been incorporated in the proposed fracture model to capture the mechanical interaction between the concrete element and the externally bonded reinforced system and to predict eventually debonding phenomena in con-crete/FRP plate interface. Suitable comparisons with available experimental results have clearly shown the reliability and the effectiveness (in terms of numerical accuracy) of the adopted fracture approach, especially in the crack pattern prediction. Fi-nally, the proposed integrated numerical model is used to pre-dict the structural response of ultra high-performance fiber-rein-forced concrete (UHPFRC) structures enhanced with embedded nanomaterials. In this case, the cohesive elements are equipped with a mixed-mode traction-separation law suitably calibrated to account for the toughening effect of the nano-reinforcement. The main numerical outcomes, presented in terms of both global structural response and final crack pattern, show the ability of the proposed approach to predict the load-carrying capacity of such structures, as well as to highlight the role of the embedded nano-reinforcement in the crack width control.
Università della Calabria. Department of Civil Engineering Dottorato di ricerca in Sciences and Engineering for the Environment, Construction and Energy. Ciclo XXXIII
Keywords: Frattura inter-elemento; Propagazione delle fessure; Strutture in calcestruzzo armato; Analisi al collasso; Sistemi di rinforzo